Formulasi dan Pengembangan Materi Pendidikan Agama Islam tentang Pembentukan Akhlak Peserta Didik Perspekif Al-Qur’an - Wini Safroh Syadiah; Cecep Anwar (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the formulation, development and delivery of Islamic religious education materials about the moral formation of students from the perspective of the Qur'an. This study uses a qualitative research method based on library research. Meanwhile, the analysis uses the side analysis method (content analysis) and description analysis. The results showed that the formulation of Islamic religious education materials on moral formation based on the Qur'an included surah al-Maidah verse 8, al-Hujurat verse 10, al-Hujurat verse 12-13, Az-Zukhruf: 67, all of these verses contains material about the necessity of Muslims having good relations socially such as establishing interactions, being kind and fair, not hating each other, saying good things, and not being hostile. The material development process is carried out by prioritizing learning material in the affective domain after the teacher first conveys and provides understanding to students. Delivering material in the affective domain is oriented towards developing the attitudes of students in their lives. So that Islamic Religious Education teachers are expected when carrying out their learning both in the classroom and outside the classroom, must be able to integrate cognitive and psychomotor values ​​with affective which is prioritized.